Outcomes of Direct Infrapectineal Buttress Plate for Quadrilateral Surface Fractures of Acetabulum Using an Anterior Intrapelvic Approach - Nadeem, Umair (Hip Pelvis, 2021)
PURPOSE: Reduction and stable fixation of the quadrilateral plate are challenging primarily due to its location in the true pelvis, limited bone stock, juxta-articular nature, and its comminution. The current study aimed to investigate the quality of reduction and functional outcomes after open reduction and internal fixation (ORIF) with infrapectineal buttress plating of the quadrilateral surface via an anterior intrapelvic approach. MATERIALS AND METHODS: We conducted a retrospective review of twenty-one patients with acetabular fractures involving quadrilateral plate operated at Ghurki Trust Teaching Hospital between January 2017 and December 2018. Radiological assessment of the quality of reduction was conducted using criteria described by Matta. Functional outcomes were evaluated using a modified Postel Merle d'Aubigné score. RESULTS: The current study included 15 males and 6 females with a mean age of 40.67±12.17 years (range, 22–62 years). The most common fracture pattern was anterior column and posterior hemi-transverse in eight patients followed by true bicolumn and T-type fractures in seven and four patients respectively. Both transverse fractures were transtectal. The quality of reduction according to Matta criteria was anatomical in 14 patients, imperfect in five and poor in two. Functional outcomes were excellent in 47.6% cases, good in 42.9%, and fair in 9.5% cases. Both patients with fair outcomes had non-anatomical reduction, and one required total hip arthroplasty at a later time. CONCLUSION: Quadrilateral plate reconstruction with an infrapectineal buttress plate applied though an anterior intrapelvic approach provides high rates of anatomical reduction and yields good functional outcomes.